Characterization of Active Species in Microwave Discharge Afterglows of N\(_2\)-H\(_2\), Ar-N\(_2\)-H\(_2\), and Ar-N\(_2\)-O\(_2\) Gas Mixtures - Hayat Zerrouki; André Ricard; Jean-Philippe Sarrette (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
This study investigates the densities of active species, including N and O atoms, N\(_2\)(A), N\(_2\)(X, v > 13) metastable molecules, and N\(_2^+\) ions, in the afterglows of N\(_2\)-H\(_2\), Ar-N\(_2\)-H\(_2\), and Ar-N\(_2\)-O\(_2\) microwave discharges. Optical emission spectroscopy and NO titration methods were used for precise calibration. The results reveal significant variations in active species densities across different gas mixtures, providing insights into optimizing plasma conditions. The -atom density is in the range of 1015cm-3 in N2 -H2, Ar - N2 and Ar - N2 - H2. It is lower by a factor of 4 in Ar - N2 - O2 gas mixtures. The -atom density coming from O2 impurity in the N2 - xH2 discharges decrease with x from 7 1013 cm-3 for x=0 to 3 1013cm-3 for x 2.5%. A strong O2 dissociation was found in the Ar-x(N2-5%O2) gas mixtures, decreasing from a full dissociation [0] = 2[O2] at x 20% to a half dissociation ([O]=[O2]) at x 50%.